Study Literatur Review: Pengaruh Status Ekonomi Keluarga Terhadap Kesejahteraan Anak - Chalisa Adya Zahra; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the influence of family economic status on child welfare and to identify the factors that mediate this relationship. The method employed is a literature review with a qualitative descriptive approach, analyzing 10 relevant scientific articles published between 2020 and 2024. The results indicate that family economic status has a significant impact on child welfare across various dimensions, including education, health, nutrition, as well as social and cognitive development. However, child welfare is also moderated by non-economic factors such as parental knowledge, parenting styles, family structure, and social capital support. In conclusion, efforts to enhance child welfare require an integrated approach that combines financial intervention with parenting education and the strengthening of social support systems